Interactions in saccharide/cation/water systems: Insights from density functional theory. (15th October 2020) - Teychené, J.; Roux-de Balmann, H.; Maron, L.; Galier, S.
Highlights: Cations and saccharides are both dehydrated in saccharide/cation/water systems. Sucrose dehydration increases according to: Li + < Na + < K + and Mg 2+ < Ca 2+ . Saccharides dehydration increase with the number of saccharide/cation interactions. The cation interactions number in water or in presence of saccharide is constant. Abstract: Interactions between saccharides and ions in aqueous solutions are of great importance in many fields (chemistry, physico-chemistry, biology, food industries). Thus, this work proposes to develop a methodology dealing with the characterization and the understanding of interactions between saccharides and cations in presence of water molecules, by a quantum mechanics approach. In the first part, the saccharide hydration properties (xylose, glucose, sucrose) in pure water are determined. Results show that the saccharide coordination numbers, as well as the saccharides hydration enthalpy, increase with the saccharide hydrophilic group number. In the second part, the influence of cations on saccharides hydration properties, and inversely, is evaluated. In saccharide/cation/water systems, the decrease in hydration enthalpy of cations and saccharides shows that both species are dehydrated and that saccharide dehydration depends on the nature of the cation. The dehydration sequence of saccharides was explained from the study of saccharide/cation interactions.